2007
DOI: 10.1149/1.2408973
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water in 1-Ethyl-3-methylimidazolium tetrafluoroborate

Abstract: Determination of water in 1-ethyl-3-methylimidazolium tetrafluoroborate has been carried out using both electrochemical and infrared spectroscopic methods. At platinum electrodes, voltammetric responses for water oxidation and reduction have been used to prepare calibration curves. It has been found that the water oxidation current at +2.4V vs Ag/AgCl is suitable for water determination to at least 40 mM. Infrared spectroscopy of water in quartz cells in the OH stretching region revealed an IR feature at 3550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…As noted in the Introduction, the seminal ionic liquid study of Cammarata et al attributed the main OH features observed in ionic liquids to symmetric and antisymmetric stretching modes of water molecules donating hydrogen bonds to two anions, i.e., water in A – ···HOH···A – solvates. All subsequent ionic liquid studies have either accepted or provided further support for this assignment. ,,, However, as seen in Figure , the spectra in most ionic liquids consist of more than the two well-defined peaks implied by this simple description.…”
Section: Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As noted in the Introduction, the seminal ionic liquid study of Cammarata et al attributed the main OH features observed in ionic liquids to symmetric and antisymmetric stretching modes of water molecules donating hydrogen bonds to two anions, i.e., water in A – ···HOH···A – solvates. All subsequent ionic liquid studies have either accepted or provided further support for this assignment. ,,, However, as seen in Figure , the spectra in most ionic liquids consist of more than the two well-defined peaks implied by this simple description.…”
Section: Results and Discussionmentioning
confidence: 94%
“…Numerous groups have previously studied the OH stretching spectra of dilute water in both dipolar , , ,, and ionic solvents. Because our interpretation builds upon this prior work, we digress to briefly summarize it here.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This second, very wide negative current maximum is likely caused by the very slow electroreduction of the residual water at the carbon electrode. The electrochemical reduction of the residual water at the glassy carbon electrode was reported by Cheek et al [ 48 ].…”
Section: Resultsmentioning
confidence: 99%